Money-Back Guarantees - Levens, Eric D.; Richter, Kevin S.; Levy, Michael J. (Seminars in Reproductive Medicine, 2013)
As fertility rates among women of advanced reproductive age have steadily increased, so has the utilization of fertility services. National health policies provide infertility treatment coverage in several developed countries; however, in the United States infertility treatment is largely privately funded, resulting in limited access to care. In response to the lack of insurance coverage, many practices offer fertility treatment on a risk-sharing or contingency fee basis. The ethical delivery of care under the auspices of these programs requires adherence to core principles including transparency, patient autonomy, and the delivery of appropriate medical care. Moreover, concerns regarding patient understanding and decision making have also been of foremost concern. Patients must be able to fully appreciate the financial and clinical implications of contingency fee programs. To further explore patient comprehension and satisfaction, we surveyed participants in our shared risk assisted reproductive technology program. The overwhelming majority of respondents felt adequately informed of and fairly charged for their treatment. Our results demonstrate that shared risk programs can receive strong endorsement from participants, which may lead to improved utilization of and perseverance with fertility treatment.
Keywords: contingency fees; payer status; assisted reproductive technology; shared risk; patient satisfaction